Perineal skin tear repair following vaginal birth; skin adhesive versus conventional suture – a randomised controlled trial - Dasrilsyah, Rima Anggrena; Kalok, Aida; Beng, Kwang Ng; Ali, Anizah; Kah, Teik Chew; Pei, Shan Lim (Informa UK Limited, 2021)
This was a prospective randomised controlled trial comparing the effects of first-degree perineal tear repair using adhesive glue versus conventional suturing in terms of pain score, wound complication and patient’s satisfaction. One hundred and twenty one women were randomised. The skin adhesive group had a significantly lower pain score at rest as well as during sitting, walking and micturition during the first week of delivery compared to the suture group. The time taken to become pain free was significantly shorter in the tissue adhesive group (3.18 vs. 8.65 days, p < .001). Only two patients who had skin glue experienced wound gaping. No significant difference was observed in the level of satisfaction between the adhesive and suture groups. Tissue adhesive is better than subcuticular suture for repairing first-degree perineal tear as it causes less pain and has shorter recovery time.